The Photographic Now: David Claerbout’s Vietnam - Hölzl, Ingrid (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2011)
David Claerbout’s video installation, Vietnam, 1967, near Duc Pho, reconstruction after Hiromichi Mine (2000), questions the “photographic now,” the present state of photography and its new relation to the present. The piece reproduces, or more exactly recomposes, a press photograph of an American airplane shot down by friendly fire. The Belgian artist travelled to the site of the accident and took a series of photos of the landscape. He then assembled these stills into a video animation onto which he superimposed the still image of the exploding plane. The result is an image whose temporality is hybrid and whose mediality is unclassifiable. This study investigates the process of digital reconstruction and animation, and the “becoming signal” of the image, and questions the possibility of reactualizing the photographic past through digital screening.